Coupling CFD and VR for advanced firefighting training in a virtual ship engine room - Darko Glujic; Goran Vukelic; Dean Bernecic; Goran Vizentin; Dario Ogrizovic (Results in Engineering)
Firefighting training using virtual reality (VR) technology has still not been used extensively in the maritime industry. One of the reasons lies in the inability of VR to accurately replicate the true dynamics of a fire. However, this shortfall can be effectively addressed by integrating computational fluid dynamics-based (CFD) models of fire spread into VR training simulations, thereby significantly enhancing the realism and educational value of these scenarios. In this study, a scenario of a fire spread inside the ship engine room has been developed. First, as a CFD analysis, whose results were then transferred to the VR environment. That approach has been tested with users who have noted that CFD-based fire gives a more realistic appearance than the generic modelled solely using the game engine.